A prime determinant in selecting dialysis modality: peritoneal dialysis patient survival - Hyunwook Kim; Dong-Ryeol Ryu (The Korean Society of Nephrology, 2017)
The number of patients with end-stage renal disease (ESRD) has rapidly increased, as has the cost of dialysis. Peritoneal dialysis (PD) is an established treatment for ESRD patients worldwide; it has a variety of advantages, including autonomy and flexibility, as well as economic benefits in many countries compared to hemodialysis (HD). However, the long-term survival rate of PD remains poor. Although direct comparison of survival rate between the dialysis modalities by randomized controlled trials is difficult due to the ethical issues, it has always been a crucial point when deciding which dialysis modality should be recommended to patients. Recently, in many countries, including the United States, Brazil, Spain, Australia, and New Zealand, the survival rate in PD patients has significantly improved. PD patient survival in Korea has also improved, but Korean PD patients are known to have higher risk of mortality and major adverse cardiovascular, cerebrovascular events than HD patients. Herein, we further evaluate why Korean PD patients had worse outcomes; we suggest that special attention should be paid to patients with diabetes, coronary artery disease, or congestive heart failure when they choose PD as the first dialysis modality in order to reduce mortality risk.